Changes in Expressions of Spermatogenic Marker Genes and Spermatogenic Cell Population Caused by Stress - Tian, Pengxiang; Zhao, Zhiming; Fan, Yanli; Cui, Na; Shi, Baojun; Hao, Guimin (Frontiers in Endocrinology, 2021)
Many young adults are in a state of stress due to social and psychological pressures, which may result in male reproductive dysfunction. To provide new insight into this phenomenon, we investigated the effect of stress on the regulation of key genes and biological events in specific stages of spermatogenesis. After establishing rat stress models of different time durations, we observed pathological changes in testis through haematoxylin and eosin staining, and analysed gene expression in testis by RNA-seq, bioinformatic analysis, and reverse transcription qPCR (RT-qPCR). Immunohistochemistry (IHC) with the TissueFAXS quantitative imaging system was used to verify changes of different population of spermatogenic cells marked by differentially expressed marker genes. Our results showed that prolonged stress can lead to pathological changes in the testes, such as thinning of the spermatogenic epithelium, a decreased number of spermatogenic epithelial cells, the disordered arrangement of spermatogenic cells, and a decreased number of mature sperms. RNA-seq revealed that key marker spermatogenesis-related genes such as Stra8, Sycp3, Piwil1, and Tnp1 had significantly decreased expression levels in chronic stress groups, and this was confirmed by RT-qPCR and IHC. Collectively, these findings suggest that chronic stress causes damaging pathological changes in testis and dysregulates the marker genes of specific stages of spermatogenesis and change the population of spermatogenic cells, which may be a critical responsible for male reproductive dysfunction.